2008
DOI: 10.1007/s11418-008-0241-4
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenes acids and saponins isolated from Licania arianeae Prance (Chrysobalanaceae)

Abstract: From the leaves and wood of Licania arianeae, ten known compounds were isolated and identified. They belong to pharmacological active triterpenes acids, including three oleanoic acids, five ursane acids, and two triterpenes saponin acids. Their structures were established by analysis of infrared, mass spectrometry, and nuclear magnetic resonance spectral data of natural triterpenes and of methyl acetyl derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This study showed the presence of terpenes, betulinic acid, ursolic acid, oleanolic acid, palmitoleic acid, hexadecanoic acid, and other compounds. Other members of Chrysobalanaceae (Tommasi et al, 2003), such as Chrysobalanus, Coupeia and Parinarium also presented similar chemical composition, with tannins, flavonoids, diterpenes, terpenes and steroids as secondary metabolites (Bilia et al, 1996;Oberlies et al, 2001;Fernandes et al, 2003;Zuque et al, 2004;Castilho et al, 2005;Carvalho et al, 2008;Carvalho and Costa, 2009).…”
Section: Resultsmentioning
confidence: 90%
“…This study showed the presence of terpenes, betulinic acid, ursolic acid, oleanolic acid, palmitoleic acid, hexadecanoic acid, and other compounds. Other members of Chrysobalanaceae (Tommasi et al, 2003), such as Chrysobalanus, Coupeia and Parinarium also presented similar chemical composition, with tannins, flavonoids, diterpenes, terpenes and steroids as secondary metabolites (Bilia et al, 1996;Oberlies et al, 2001;Fernandes et al, 2003;Zuque et al, 2004;Castilho et al, 2005;Carvalho et al, 2008;Carvalho and Costa, 2009).…”
Section: Resultsmentioning
confidence: 90%
“…These are terpenes, betulinic acid, ursolic acid, oleanolic acid, palmitoleic acid, hexadecanoic acid, and other compounds. Other members of Chrysobalanaceae [43], such as Chrysobalanus, Coupeia and Parinarium also presented similar chemical composition: flavonoids, tannins, diterpenes, terpenes and steroids as secondary metabolites [44,45,46] herbs and spices may not only be due to its total phenolics but also to the other groups of phytochemicals present. This finding marks a significant contribution as a prevention of cancer especially that these herbs and spices are readily available and can be found as condiments to any cooking procedure.…”
Section: Legend: + Present -Absentmentioning
confidence: 94%